(untitled) - Townsley, Philip (Rome, 1996)
This document is intended for agriculture development specialists, aquaculture project managers, and officials and specialists involved in the planning and management of aquaculture activities. It is intended to provide an introduction to Rapid Rural Appraisal (RRA) and Paticipatory Rural Appraisal (PRA) for people working in these fields. The principle components of these two approaches to information collection and planning are described along with the various tools used with a case study to illustrate their use and some of the issues they raise. Possible applications of the approaches for those involved in aquaculture development are given and an outline provided of the sorts of planning and institutational context where they can best be applied. The problems and shortcomings of the approaches are also discussed and guidelines given for the use of alternative approaches to information gathering and planning.
Quy hoạch và quản lý nuôi trồng thủy sản
Keywords: fisheries